Successful user experience : strategies and roadmaps - Rosenzweig, Elizabeth (Elsevier, 2015)
Successful User Experience: Strategy and Roadmaps provides you with a hands-on guide for pulling all of the User Experience (UX) pieces together to create a strategy that includes tactics, tools, and methodologies. Leveraging material honed in user experience courses and over 25 years in the field, the author explains the value of strategic models to refine goals against available data and resources. You will learn how to think about UX from a high level, design the UX while setting goals for a product or project, and how to turn that into concrete actionable steps. After reading this book, y.